Transmembrane Tumor Necrosis Factor Controls Myeloid-Derived Suppressor Cell Activity via TNF Receptor 2 and Protects from Excessive Inflammation during BCG-Induced Pleurisy - Chavez-Galan, Leslie; Vesin, Dominique; Uysal, Husnu; Blaser, Guillaume; Benkhoucha, Mahdia; Ryffel, Bernhard; Quesniaux, Valérie F. J.; Garcia, Irene (Frontiers in Immunology, 2017)
Pleural tuberculosis (TB) is a form of extra-pulmonary TB observed in patients infected with Mycobacterium tuberculosis. Accumulation of myeloid-derived suppressor cells (MDSC) has been observed in animal models of TB and in human patients but their role remains to be fully elucidated. In this study, we analyzed the role of transmembrane TNF (tmTNF) in the accumulation and function of MDSC in the pleural cavity during an acute mycobacterial infection. M. bovis BCG-induced pleurisy was resolved in mice expressing tmTNF, but lethal in the absence of TNF. Pleural infection induced MDSC accumulation in the pleural cavity and functional MDSC required tmTNF to suppress T cells as did pleural WT MDSC. Interaction of MDSC expressing tmTNF with CD4 T cells bearing TNFR2, but not TNFR1, was required for MDSC suppressive activity on CD4 T cells. Expression of tmTNF attenuated Th1 cell-mediated inflammatory responses generated by the acute pleural mycobacterial infection in association with effective MDSC expressing tmTNF and interacting with CD4 T cells expressing TNFR2. In conclusion, this study provides new insights into the crucial role played by the tmTNF/TNFR2 pathway in MDSC suppressive activity required during acute pleural infection to attenuate excessive inflammation generated by the infection.